Intra- and Inter-observer Variability of Measurements of the Laxity Index on Stress Radiographs Performed with the Vezzoni-Modified Badertscher Hip Distension Device - Bertal, Mileva; Vezzoni, Aldo; Houdellier, Blandine; Bogaerts, Evelien; Stock, Emmelie; Polis, Ingeborgh; Deforce, Dieter; Saunders, Jimmy H.; Broeckx, Bart J.G. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives To describe and evaluate the accuracy, intra- and inter-observer variability of the laxity index (LI), used to quantify hip laxity on stress radiographs obtained with the Vezzoni-modified Badertscher distension device (VMBDD).Methods Stress radiographs of 10 dogs obtained with the VMBDD were measured three times by an experienced observer. Six participants with different backgrounds (two ECVDI residents, two PhD students, two veterinary assistants) followed a short presentation and performed subsequently the measurements four times in two separate sessions. The effect of self-learning, feedback and specialization on the accuracy of the measurements was assessed.Results While the intra- and inter-observer variability were in agreement with other studies, the results of the experienced observer indicated that the variability can be very low. Neither feedback nor self-learning improved the results. A high degree of experience in radiographic assessment was not necessary to perform the measurements correctly.Clinical Significance As the LI measurements were acceptable after a short presentation, they support the use of VMBDD for a complete and correct in-house evaluation of the hip joint by trained clinicians. However, we propose that, in the context of screening, measurements should be performed by a limited number of experienced examiners, to limit the impact of the inter-observer variability.
Keywords: hip; laxity index; intra-observer; inter-observer; variability